Tuberculosis Disease Intervention through Education for the Community of Uteunkot Village, Muara Dua District, Lhokseumawe City - Vera Novalia; Wheny Utariningsih; Noviana Zara (LPPM Universitas Malikussaleh, 2022)
Until now Tuberculosis has become a health problem in Indonesia which causes high mortality found in 8,471 cases. In Lhokseumawe City with the highest CNR of tuberculosis cases in Aceh Province, around 351 per 100,000 population. One of the efforts to prevent TB transmission is by avoiding contact with the community. It is necessary to educate about TB disease in terms of symptoms, transmission and prevention. This research involved around 90 people with a quasi-experimental research type of one group pretest-posttest design. Data was collected using a check list sheet and observation. The results of this activity indicated that there was an increase in respondents' knowledge of knowledge and prevention of Tuberculosis with the less category of 22 people (24.4%). Respondents level of knowledge in the sufficient category as many as 54 people (60.0%). Meanwhile, respondents whose level of knowledge was in the good category were 14 people (15.6%). but after being given education, the level of knowledge of respondents about tuberculosis increased, namely enough with the number of 70 people (77.8%). poor and good categories as many as 19 people (21.1%) while less a little (1.1%). It is hoped that the provision of TB disease education can increase knowledge in efforts to prevent TB transmission will increase for a better quality of life in the health sector.